2003
DOI: 10.1104/pp.102.017814
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the GCC-Box in Jasmonate-Mediated Activation of the PDF1.2 Gene of Arabidopsis

Abstract: The PDF1.2 gene of Arabidopsis encoding a plant defensin is commonly used as a marker for characterization of the jasmonate-dependent defense responses. Here, using PDF1.2 promoter-deletion lines linked to the ␤-glucoronidase-reporter gene, we examined putative promoter elements associated with jasmonate-responsive expression of this gene. Using stably transformed plants, we first characterized the extended promoter region that positively regulates basal expression from the PDF1.2 promoter. Second, using promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
268
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(283 citation statements)
references
References 65 publications
8
268
1
2
Order By: Relevance
“…In the case of AtERF2, its role as a positive regulator of MeJA response was confirmed, as had previously been suggested in plants overexpressing AtERF2 (Brown et al, 2003). Additionally, a reduction in disease symptoms relative to wild type after inoculation with F. oxysporum was observed, supporting a role for AtERF2 as a positive regulator of disease resistance.…”
Section: What Was Shownsupporting
confidence: 62%
“…In the case of AtERF2, its role as a positive regulator of MeJA response was confirmed, as had previously been suggested in plants overexpressing AtERF2 (Brown et al, 2003). Additionally, a reduction in disease symptoms relative to wild type after inoculation with F. oxysporum was observed, supporting a role for AtERF2 as a positive regulator of disease resistance.…”
Section: What Was Shownsupporting
confidence: 62%
“…The activation of defense responses by ethylene has previously been associated with the activity of transcription factors binding the GCC box in defense promoters, resulting in the induction of antimicrobial genes such as PDF1.2 and chitinases in Arabidopsis (Ohme-Takagi and Fujimoto et al, 2000;Brown et al, 2003). When transgenic hairy roots containing the 43GCC::luciferase construct were challenged with R. solani, an early induction of the reporter gene suggested that an ethylene-mediated response was induced at the initial stages of infection, while an additional induction peaking at 14 h suggested a secondary phase of activity of the GCC element.…”
Section: Discussionmentioning
confidence: 99%
“…Two kilobases of sequence upstream of the predicted start codon of each of the VvHT1 to -5 and VvcwINV genes was obtained from the published grapevine PN40024 genome sequence (Jaillon et al, 2007) and analyzed for putative regulatory motifs associated with stress-induced transcription using the PLACE database (Higo et al, 1999). A number of motifs were identified: GCC box (Brown et al, 2003), MYC recognition (Abe et al, 1997), T/G box (Boter et al, 2004), wound response element (Palm et al, 1990), and abscisic acid response elements (ABREs; Choi et al, 2000;Hattori et al, 2002). Figure 3 also shows the presence of Suc-responsive motifs (SURE1, Suc box 3) shown previously by Cakir et al (2003) to be involved in the transcriptional regulation of VvHT1.…”
Section: Identification Of Aba Regulatory Motifs In the Vvht5 Promotermentioning
confidence: 99%
“…The presence of regulatory motifs associated with stress-induced transcription in a 2-kb promoter region from the published grapevine PN40024 genome sequence is shown. Recognition sequences are as follows: GCC box (GCCGCC; Brown et al, 2003), T/G box (AACGTG; Boter et al, 2004), MYC (CACATG; Abe et al, 1997), ABRE (ACGTGG/TC; Hattori et al, 2002), and wound response element (WRE; AAA/TGTATCC/GA; Palm et al, 1990). Also shown are the Suc-responsive motifs SURE (ATA-GAAA) and Suc box 3 (AAATCA----AA), identified by Cakir et al (2003) to be involved in the transcriptional regulation of VvHT1.…”
Section: Biotrophic Pathogen Infection and Wounding Induce The Aba Bimentioning
confidence: 99%